2014
DOI: 10.3109/13625187.2014.957825
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in sexual and reproductive health of Roma people who live in settlements in Serbia

Abstract: Although data on the SRH of the general population of women in Serbia are far from being satisfactory, those for women who live in Roma settlements are much worse. Political actions aimed at the empowerment of Roma women in the spheres of education, employment and health promotion have been implemented with the hope that they might improve the SRH of this vulnerable population group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 5 publications
1
23
0
3
Order By: Relevance
“…Due to the difficult access to health care caused by various factors (large distance of the health centre, insufficient hygiene, discrimination against Roma shown in health care institutions, lack of access to prescribed medication due to financial reasons, etc.) a part of the Roma population visits the doctor only in serious health conditions (12)(13)(14)(15)(16)(17)(18). However, the Roma population prefers births in a hospital or in a healthcare institution.…”
Section: S26mentioning
confidence: 99%
“…Due to the difficult access to health care caused by various factors (large distance of the health centre, insufficient hygiene, discrimination against Roma shown in health care institutions, lack of access to prescribed medication due to financial reasons, etc.) a part of the Roma population visits the doctor only in serious health conditions (12)(13)(14)(15)(16)(17)(18). However, the Roma population prefers births in a hospital or in a healthcare institution.…”
Section: S26mentioning
confidence: 99%
“…However, scientific studies mostly do not document the whole region, as most are only focused on single countries (e.g. Andreassen et al 2018;Cook et al 2013;Dimitrova et al 2013;Dimitrova et al 2018;Kamberi et al 2015;Kósa et al 2015;Nikolic et al 2015;Sedlecky et al 2015;Walfisch et al 2013;Zeljko et al 2013). Findings on other determinants of health in CEE Roma are even more varied and sparse.…”
Section: Figure 12 Health Indicators For Roma and The General Populamentioning
confidence: 99%
“…Peters et al (91) found that Gypsies and Travellers and African Caribbean participants had a higher use of midwife services than participants from the White population and Pakistani Muslim population; though the authors acknowledge that this may be due to higher fertility rates. Evidence relating to Roma women's use of maternity services in Eastern and Central Europe suggests that in general, Roma women engage less with maternity services than non-Roma women (59,82,93,95). For example, in a study in Serbia, 6% of Roma women compared to 1% of non Roma women had no antenatal appointments (95), and in a study in Turkey (66), slightly more non-Roma than Roma women (92.9% and 82.9% respectively) had home visits from midwives.…”
Section: Uptake Of Servicesmentioning
confidence: 99%
“…Evidence relating to Roma women's use of maternity services in Eastern and Central Europe suggests that in general, Roma women engage less with maternity services than non-Roma women (59,82,93,95). For example, in a study in Serbia, 6% of Roma women compared to 1% of non Roma women had no antenatal appointments (95), and in a study in Turkey (66), slightly more non-Roma than Roma women (92.9% and 82.9% respectively) had home visits from midwives.…”
Section: Uptake Of Servicesmentioning
confidence: 99%
See 1 more Smart Citation